SETTING SOSIAL DAN BUDAYA DALAM AL-QUR’AN SEBAGAI PEDOMAN PELAKSANAAN DAKWAH - Budi Riva; Bukhari Bukhari (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2020)
The contents of the Qur'an are loaded with social and cultural settings in the implementation of da'wah. This article explains the existence of the Qur'an loaded with social and cultural settings as a guide to preaching. The purpose of this discussion is to see how the Qur'an describes the effort in da'wah in terms of socio-cultural aspects. This research is a descriptive-qualitative type library research, which describes the situation of the socio-cultural reality of the community as a setting of the Qur'an in the implementation of da'wah. Furthermore, it draws reality as a feature, situation or phenomenon in the implementation of da'wah which must be understood historically and philosophically from the culture that developed in society, then internalized with Islamic values.